Comparisons of Children with and without Type I Diabetes on Hand and Visual Motor Integration Skills and on Participation in Daily Activities. Issue 4 (August 2022) - Kılıçöz, Mehtap; Kutlutürk Yıkılmaz, Seval; Yüksel, Ayşegül; Kaya Kara, Özgün
Our aim in this study was to compare hand skills, visual-motor integration skills, and participation in daily living activities of children with and without Type 1 diabetes (T1DM). In this prospective cross-sectional study, we included 44 children with T1DM (17 males, 27 females; aged 8-12 years) and a control group of 45 healthy age-matched children without T1DM (22 males, 23 females). We compared group scores on the Jebsen-Taylor Hand Function Test (JTHFT), the Beery-Buktenica Developmental Visual Motor Integration Test (Beery VMI), and the Participation and Environment Measure - Children and Youth (PEM-CY). JTHFT and Beery VMI scores of children with T1DM were significantly lower than those of the control group ( p ≤ 0.005). On the PEM-CY, children with T1DM were found to have more participation barriers in the community than controls. Relative deficits in hand skills and visual motor integration of children with T1DM should be managed with greater attention and assistance.